Electronic Structures of Homodinuclear Platinum(II), Palladium(II) and Gold(I) Complexes Featuring Janus-type Benzoxazolin-2-ylidene Linkers - Ha, Nguyen Van; Hang, Nguyen Thi Thu (VNU Journal of Science: Natural Sciences and Technology; Vol 37 No 1, 2021)
Electronic structures of a series of three homodinuclear platinum(II), palladium(II) and gold(I) complexes featuring Janus-type benzoxazolin-2-ylidene bridges and N,N-diisopropyl benzimidazolin-2-ylidene auxiliary ligands have been investigated. The gas-phase molecular structures of all compounds were first optimized using B3PW91 functional and SDD/6-31G(d) combination of basis sets. The nature of their frontier orbitals were then examined. The higher energy occupied molecular orbitals are predominantly d orbital of the metal in combination with p orbital of N,N-diisopropyl benzimidazolin-2-ylidene. On the other hand, the lower energy unoccupied molecular orbitals are p orbitals of the benzoxazolin-2-ylidene. TD-DFT calculations reveal that all the complexes require high energy ultraviolet photon for excitation and photoexcitations form excited state with decreased electron density on metal centers.